SPINOZAâ€™S GOD METAPHYSICAL CONCEPTION OF THE DIVINE - Adian, Donny Gahral (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2013)
The discourse on conception of God has occupied fundamental position either in theology or philosophy. In philosophical one, this conception could be traced since very ancient time of Greek until modern era of philosophy with various metaphysical view points. Spinoza was one of the philosophers whose famous metaphysical conception of God is basically a critique toward transcendental paradigm that detaches God from His creation entirely. In this case, he develops his own metaphysical system that rests upon â€œsubstanceâ€ as focal category. This paper seeks to discuss Spinozaâ€™s metaphysical conception of God which represents his theological monism through his wide range elaboration on â€œsubstanceâ€.